Polarization shaping of Poincaré beams by polariton oscillations - Colas, David (2015)
We propose theoretically and demonstrate experimentally the generation of light pulses whose polarization varies temporally to cover selected areas of the Poincaré sphere with both tunable swirling speed and total duration (1 ps and 10 ps, respectively, in our implementation). The effect relies on the Rabi oscillations of two polariton polarized fields excited by two counter-polarized and delayed pulses. The superposition of the oscillating fields result in the precession of the Stokes vector of the emitted light while polariton lifetime imbalance results in its drift from a circle of controllable radius on the Poincaré sphere to a single point at long times. The positioning of the initial circle and final point allows to engineer the type of polarization spanning, including a full sweeping of the Poincaré sphere. The universality and simplicity of the scheme should allow for the deployment of time-varying full-Poincaré polarization fields in a variety of platforms, timescales, and regimes.